2014
DOI: 10.3945/ajcn.113.077198
|View full text |Cite
|
Sign up to set email alerts
|

Obesity interferes with the orosensory detection of long-chain fatty acids in humans

Abstract: Altogether, these data strongly suggest that obesity may interfere with the orosensory system responsible for the detection of free long-chain fatty acids in humans. This trial was registered at clinicaltrials.gov as NCT02028975.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 33 publications
8
60
1
7
Order By: Relevance
“…Obese individuals have, on average, a greater liking for sweetness and high-fat foods (7). However, the impact of BMI, as variable in the oral lipid sensitivity, remains a matter of debate since some studies report a negative correlation (204,206,207), while no association is found in others (32,127,205). These inconsistencies are likely due to the difficulties inherent in comparing sensory experiences across individuals using a psychophysical approach (3-AFC procedure), especially when a sensation that is not easily identifiable is studied.…”
Section: B Obesity Also Affects the Orosensory Detection Of Lipidsmentioning
confidence: 88%
“…Obese individuals have, on average, a greater liking for sweetness and high-fat foods (7). However, the impact of BMI, as variable in the oral lipid sensitivity, remains a matter of debate since some studies report a negative correlation (204,206,207), while no association is found in others (32,127,205). These inconsistencies are likely due to the difficulties inherent in comparing sensory experiences across individuals using a psychophysical approach (3-AFC procedure), especially when a sensation that is not easily identifiable is studied.…”
Section: B Obesity Also Affects the Orosensory Detection Of Lipidsmentioning
confidence: 88%
“…Adding clinical relevance to these findings, a single nucleotide polymorphism in the CD36 gene of obese African-American women has been associated with an increase in the detection threshold for fat (64). In addition, a study in obese men found increased detection threshold for fat compared with lean controls (74). Thus, the information currently available allows us to identify CD36, TRPM5, GPR40, and GPR120 as candidate fattaste receptors.…”
Section: Fat Tastementioning
confidence: 88%
“…Contrairement aux rongeurs, l'existence d'une corrélation entre obésité et sensibilité de la lipido-détection orale reste dé-battue chez l'homme puisque certaines études rapportent une association entre l'indice de masse corporelle (IMC) et le seuil de détection des lipides (Stewart et al, 2010(Stewart et al, , 2011, alors que d'autres ne trouvent aucune corrélation récurrente entre ces deux paramètres (Mattes, 2011a;Stewart et Keast 2012;Chevrot et al, 2014). Cette différence inter-espèce pourrait puiser son origine non seulement chez les sujets eux-mêmes (hétérogénéité génétique et des habitudes alimentaires), mais également dans l'approche méthodologique utilisée.…”
Section: éTudes Humainesunclassified
“…Ces différentes limitations pourraient également expliquer la grande variabilité des seuils de détec-tion des lipides observée chez l'homme, qu'il soit de poids normal ou obèse. Toutefois, une étude récente utilisant la méthode 3-AFC rapporte que les sujets les moins aptes à détecter les lipides étaient tous obèses (IMC ≥ 30 kg/m 2 ) et se distinguaient des autres participants, qu'ils soient obèses ou non, par une surconsommation d'aliments gras (Chevrot et al, 2014). Il est donc possible que la relation entre obésité, performance de la lipido-détection orale et choix alimentaire puisse également exister chez l'homme, bien qu'elle ne semble pas être systé-matique, contrairement à ce qui est trouvé chez les rongeurs.…”
Section: éTudes Humainesunclassified
See 1 more Smart Citation